Why Do Some Consumers Still Prefer In-Store Shopping? An Exploration of Online Shopping Cart Abandonment Behavior - Wang, Siqi; Ye, Ye; Ning, Binyao; Cheah, Jun-Hwa; Lim, Xin-Jean (Frontiers in Psychology, 2022)
Shopping cart abandonment remains a challenge for many e-retailers despite the continued growth of the e-commerce industry worldwide. However, the issue of online shopping cart abandonment (OSCA) has not been explored extensively in the literature. Grounded by the stimulus-organism-response (S-O-R) model, this study explores a sequential mediation model comprising consumers’ wait for lower prices as an antecedent, hesitation at checkout and OSCA as mediators, perceived transaction inconvenience as a moderator, and decision to buy from a land-based retailer (DBLR) as an outcome. An online questionnaire was designed and distributed to 883 online consumers in Mainland China. Partial least squares-structural equation modeling (PLS-SEM) was employed to analyze the survey data. The results show that waiting for lower prices positively influences hesitation at checkout, and subsequently, impacts both OSCA and DBLR. Hesitation at checkout and OSCA play sequential mediating roles in the framework path. In addition, perceived transaction inconvenience strengthens the relationship between waiting for lower prices and hesitation at checkout. Overall, this study contributes to theory and serves as a guideline for e-retailers in reducing the OSCA rate.